PERSEPSI PENGUNJUNG TENTANG FASILITAS WISATA DI OBJEK WISATA LEMBAH HARAU KABUPATEN LIMA PULUH KOTA - Fatimah, Sithy; Silfeni, Silfeni; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2014)
The purpose of research is to to know Perceptions Visitors About Facilities Attractions Tourism In Harau Valley. This study was descriptive quantitative. Population of 160 242 visitors in the attraction. Selection of the study sample using technique using incidental sampling as many as 100 people. Data collection using a questionnaire based on a Likert Scale that have been tested for validity and reliability. Perception research results Facility Visitors About Tourism In Harau Valley Attractions categorized quite well with the average value of 172.01 which is at 185.9 157,1- range. While based on each of the indicators, namely: (1) the form of tourist facilities belong to the poor category with an average value of 49.46 is in the range 53.9 42,7- scores, (2) the functions belonging to the category of tourist facilities quite well with the average value of 34.04 is in the range of 37.6 31,4- scores, (3) the location of tourist facilities belong to the category of fairly well with the average value of 46.65 scores were in the range 39.4 - 47.6, (4) the quality of tourist facilities belong to the category of fairly well with the average value in the range of 42.86 39,8- score of 48.2.